2014
DOI: 10.1039/c4ra00048j
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid promoted C–C and copper-catalyzed C–O bond formation: synthesis of neoflavans

Abstract: An intramolecular [Cu]-catalyzed C–O bond formation for the synthesis of neoflavans is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…The flavan 7 p has been isolated from whole plant of Ageratum conyzoides along with four other compounds, while, the 4′‐hydroxy‐7‐methoxy flavan 7 q is known as one of the anti‐feedant compounds isolated from Lycoris raliata . We presumed that the target flavan 7 p could be achieved by a copper catalyzed intramolecular Buchwald‐Hartwig cyclization of the secondary alcohol 4 p . Whereas, the flavan 7 q could be achieved from 4 q under established conditions and debenzylation protocol .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flavan 7 p has been isolated from whole plant of Ageratum conyzoides along with four other compounds, while, the 4′‐hydroxy‐7‐methoxy flavan 7 q is known as one of the anti‐feedant compounds isolated from Lycoris raliata . We presumed that the target flavan 7 p could be achieved by a copper catalyzed intramolecular Buchwald‐Hartwig cyclization of the secondary alcohol 4 p . Whereas, the flavan 7 q could be achieved from 4 q under established conditions and debenzylation protocol .…”
Section: Resultsmentioning
confidence: 99%
“…We presumed that the target flavan 7 p could be achieved by a copper catalyzed intramolecular Buchwald‐Hartwig cyclization of the secondary alcohol 4 p . Whereas, the flavan 7 q could be achieved from 4 q under established conditions and debenzylation protocol . Thus, copper catalyzed intramolecular Buchwald‐Hartwig cross‐coupling of 4 p afforded the naturally occurring 7‐methoxy‐3′,4′‐methylenedioxyflavan 7 p in 79 % (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…When the same reaction was run with two equivalents of 2b, 92% yield of 3ab was obtained ( Table 1, entry 8). Various acids were tested for the reaction of 1a with 2b ( Table 1, entries [8][9][10][11][12][13][14][15]. All acids tested were effective for this reaction except for silica gel and 3ab was obtained in good to excellent yields.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…24,25) Recently, Reisman et al reported the synthesis of 2,2-dialkylchromane prepared from a tertiary alcohol with bromoarene in the total synthesis of (+)-Psiguadial B 26) by copper-catalyzed coupling reactions, which were originally investigated by Satyanarayana and colleagues. 27,28) In the Satyanarayana's catalyst system, a bridgehead alcohol might be necessary 26) or substitutions in 4-positions 28) are required to enhance the reactivity by Thorpe-Ingold effect. 29) Furthermore, the product yields of reported compounds were unsatisfactory except in some cases.…”
mentioning
confidence: 99%
“…We considered that the formation of inactive copper complexes was suppressed and consequently acceler-ated the reaction rate to improve the yield. [23][24][25] Other reported reaction conditions, such as using 1,10-phenanthroline 35) or 2,2′-bipyridyl with copper iodide, [26][27][28] gave low product yields. Finally, a deprotection process was conducted by treating the protected PMC (7) with BBr 3 to give the desired PMC (2) with a good yield (Chart 4).…”
mentioning
confidence: 99%